Cross transferability of SSRs to five species of Araucariaceae: a useful tool for population genetic studies in Araucaria araucana - Moreno, Angela Carolina (2011)
Cross-species amplification of microsatellites is a common procedure to obtain suitable markers to be used in population genetic studies. Primers designed for one (source) species are used to amplify homologous loci in related (target) species. It is expected that phylogenetically close species will share a higher proportion of markers, and genetic distance could be a useful parameter to predict successful transferability between different taxonomic groups. We analyzed twenty-two primer pairs developed for Araucaria angustifolia (Bertol.) Kuntze in five target species of the Araucariaceae family. The results were summarized in vectors of presence and absence of bands and compared through the Jaccard similarity index. Using the sequences of eight published genes, genetic distances between pairs of species were estimated and related to transferability rate using Pearson correlations. Successful transfer rate ranged from 31.8 to 77.3%, being these among the highest reported for plants. The highest transfer rate was observed between the South American species. The transferability was confirmed sequencing seven fragments amplified in A. araucana (Molina) K. Koch, and using the best five to estimate genetic diversity parameters in a natural population of this Andean coniferous.